2005
DOI: 10.1128/ec.4.4.765-774.2005
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Ligases of Trypanosoma brucei

Abstract: The mitochondrial DNA of Trypanosoma brucei, termed kinetoplast DNA or kDNA, consists of thousands of minicircles and a small number of maxicircles catenated into a single network organized as a nucleoprotein disk at the base of the flagellum. Minicircles are replicated free of the network but still contain nicks and gaps after rejoining to the network. Covalent closure of remaining discontinuities in newly replicated minicircles after their rejoining to the network is delayed until all minicircles have been r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
87
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 36 publications
2
87
0
Order By: Relevance
“…Others have suggested that the antipodal sites are organized into subdomains populated by different enzyme activities (9,15). Multiple lines of evidence support this view.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Others have suggested that the antipodal sites are organized into subdomains populated by different enzyme activities (9,15). Multiple lines of evidence support this view.…”
Section: Discussionsupporting
confidence: 53%
“…Multiple lines of evidence support this view. First, Okazaki fragment-processing enzymes Pol ␤ and SSE1 appear to colocalize (12), while TopoII mt and Ligk ␤ do not precisely colocalize (9). Second, ethanolic-phosphotungstic acid staining showed regions that differ in staining intensity, indicating the variability of protein concentration in different regions of the antipodal sites (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2D and 5B). In the case of several other kDNA replication proteins silenced by using RNAi (1,(25)(26)(27), it has been found that, although kDNA has not been properly replicated, it has nevertheless gone through a segregation process, which resulted in an uneven segregated networks, creating one cell with a minimal kDNA network and another with a very small nonfunctional kDNA (23). Such a process led to shrinkage of the network and eventually to kDNA loss.…”
Section: Discussionmentioning
confidence: 99%
“…Within these sites, subsequent steps of replication occur, catalyzed by enzymes specifically localized therein. These reactions are thought to include primer removal by a structure-specific endonuclease-I (SSE1) (15-17) and repair of some (but not all) of the minicircle gaps by a DNA polymerase ␤ (18, 19) and a DNA ligase (20,21). Finally, the progeny minicircles, still containing at least one nick or gap, are attached to the edge of the kDNA network by an antipodal topoisomerase II (22, 23).…”
mentioning
confidence: 99%